Digitization: awareness and challenges among professional in National Archive of Malaysia / Ahmad Amir Asnawi Sabri ...[et al.] - Sabri, Ahmad Amir Asnawi; Husain, Mohd Khairul Asyraf; Daharin, Mohamad Firdaus; Zainudin, Muhamad Zulhafeeq; S Baharuddin, Shafiq (2014)
This chapter is to focus on several part which consist of the context of the study, the problem statement, objective of the study, background of the organization, methodology, scope of the study, and significance.